Thyroid diseases in children and adults with celiac disease: A cross-sectional study - Ramin Niknam; Heydar Baseri; Laleh Mahmoudi; Mohammad Reza Fattahi; Ebrahim Fallahzadeh Abarghooee; Ali Zamani (Babol University of Medical Sciences, 2024)
Background: There are few reports evaluating different factors, including the severity of duodenal histopathological findings and serological levels of celiac disease (CD), in increasing the probability of thyroid diseases (TD) in adults and children with CD, so, we designed this research. Methods: CD was defined as Marsh type 2 or higher in duodenal histopathology and serological levels of anti-transglutaminase antibodies (anti-tTG) equal to or greater than 18 IU/ml. To assess the likelihood of TD in CD patients, logistic regression analysis was employed. Results: 538 patients were included in this study. Of these, 354 (65.8%) were females and 184 (34.2%) were males. 370 (68.8%) patients were children. Overall, 57 (10.6%) patients had TD, of which 49 (9.1%) had hypothyroidism and 8 (1.5%) had hyperthyroidism. Adults had a significantly higher probability of developing TD than children (OR 1.9; 95% CI 1.1-3.4; P = 0.03). The odds of developing TD were also significantly higher in patients with family marriage in parents (OR 2.3; 95% CI 1.1-4.7; P = 0.03). Other variables such as gastrointestinal symptoms, anti-tTG levels, and severity of Marsh classification did not exhibit a substantial rise in the likelihood of TD development. Conclusion: The study findings indicated that the likelihood of developing TD in CD patients can be linked to advancing age and having family marriage in parents, while there was no significant association observed with anti-tTG levels, severity of histological damage, and gastrointestinal symptoms.